2015
DOI: 10.1590/so100-720320150005207
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da atividade sexual precoce

Abstract: IntroduçãoA adolescência é caracterizada por acentuadas mudanças corporais e psíquicas devidas à crescente produção hormonal que influencia o desenvolvimento emocional e o comportamento. A Organização Mundial da Saúde (OMS) considera adolescência o período entre 10 e 19 anos de idade. No Brasil, o Estatuto da Criança e do Adolescente (Lei nº 8.069/1990) a define como a faixa etária entre 12 e 18 anos 1 . As implicações jurídicas dessas definições são, às vezes, contrárias ao direito da população adolescente e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
3
0
7
Order By: Relevance
“…It is also worth mentioning that although the Brazilian Penal Code presumes a crime of any sexual act with children under 14 years of age, the age of first sexual intercourse among adolescents has been increasingly lower (Gonçalves et al, 2015;Lara;Abdo, 2015). According to Gonçalves et al (2015), the average age of onset of sexual life is 14.9 years old, however, a survey carried out by the authors showed that the beginning of sexual life between 10 and 14 years old has been frequent, mainly among male adolescents with less schooling and low economic level.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth mentioning that although the Brazilian Penal Code presumes a crime of any sexual act with children under 14 years of age, the age of first sexual intercourse among adolescents has been increasingly lower (Gonçalves et al, 2015;Lara;Abdo, 2015). According to Gonçalves et al (2015), the average age of onset of sexual life is 14.9 years old, however, a survey carried out by the authors showed that the beginning of sexual life between 10 and 14 years old has been frequent, mainly among male adolescents with less schooling and low economic level.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…According to Gonçalves et al (2015), the average age of onset of sexual life is 14.9 years old, however, a survey carried out by the authors showed that the beginning of sexual life between 10 and 14 years old has been frequent, mainly among male adolescents with less schooling and low economic level. For Lara and Abdo (2015), several factors contribute to the beginning of early sexual life, such as longer time at home without supervision and without occupation, low education, low socioeconomic level and drug use. In the area of health, the age of the first sexual relation between adolescents, 10 to 14 years, occurs at a time in life when the adolescent often does not have a set of conditions, whether emotional or knowledge, that allows them to manage situations that may bring consequences for their health in the future, such as always adopting good contraceptive/preventive practices.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroborando este hecho, un estudio mostró que la sexarca precoz está asociada principalmente con ser negra, hija de madre adolescente y padres separados, bajo nivel de instrucción y socioeconómico, baja autoestima, inseguridad, influencia de los medios de comunicación, desconocimiento sobre infecciones sexualmente transmisibles, influencia social y del medio en que vive, falta de diálogo con los padres, insistencia del compañero, falta de educación sexual en la escuela, desempleo, consumo de drogas y alcohol, no practicar religión e influencia de los amigos que ya tuvieron relación sexual (7) .…”
Section: Discussionunclassified
“…Alguns fatores que podem colaborar para o início precoce da atividade sexual são despender muito tempo ocioso e não supervisionado, contato com cenas eróticas podem promover, além da precocidade da iniciação da vida sexual, a busca por sensações sexuais Brazilian Journal of Development, Curitiba, v.7, n.9, p. 92035-92050 sep. 2021 também precoce. Falta de emprego, pouco conhecimento sobre o HIV, uso de drogas, abuso sexual na infância e a crença de que a maioria das pessoas em sua idade já iniciaram sua vida sexual podem, ainda, promover a entrada precoce da vida sexual (LARA e ABDO, 2015). Contudo, a problemática da apresentação das drogas se é dado através do álcool, que apresenta o papel de 'indutor' a outras drogas.…”
Section: Referencial Teóricounclassified